Different traditions, lives that intertwine: The meeting of two artists in Manaus (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
Two women artists from different traditions - the indigenous artist-performer and the non-indigenous artist-performer - met for the first time when performing an artistic performance together and discovered affinities that led them to tread a path where life and art intertwine, establishing a dialogue between the different knowledges of each one, seeking new possibilities of creation for their poetic practices, reinventing themselves with each new challenge that presents itself, such as the COVID-19 pandemic.
Keywords: Indigenous People; Performance; Women artists; Tradition